A Tale of Two Rangatira: Rewi Maniapoto, Wiremu Tamihana and the Waikato War - O'Malley, Vincent (Waka Kuaka, 2016)
The depiction of Ngāti Maniapoto generally and Rewi Maniapoto in particular as extremists with an almost fanatical determination to fight the British runs deep in the historiography of the New Zealand Wars, all the way from John Featon to G. W. Rusden, James Cowan to Keith Sinclair and others. And a corollary argument is that Ngāti Maniapoto, through their actions and gestures, provoked the Crown (whether justly or unjustly) into launching an invasion of the Waikato district in July 1863, and then escaped virtually scot-free from the subsequent confiscation of lands. Even fierce critics of the governmentâ€™s actions in the 1860s thus end up at least partly legitimising or justifying war and confiscation by reference to the supposed partial provocation of Ngāti Maniapoto and their leader. Their stance is often contrasted with that of Wiremu Tamihana, who is said to have been leader of the â€œmoderateâ€ Kā«ngitanga faction. This article argues that the differences between the two rangatira have been overstated. Wiremu Tamihana and Rewi Maniapoto had more in common than divided them. Furthermore, rather than conceptualising this in terms of â€œmoderateâ€ versus â€œextremistâ€, the difference between the two rangatira might be better conceptualised as idealist versus realist.Â Considered within the context of Māori custom, moreover, both men operated within the accepted limits of chiefly behaviour, which was concerned above all with questions of mana.